Optimization design of BNCT neutron source and moderating body based on accelerator 7Li(p, n) reaction - GUO Zhiqi; LIU Changqi; ZHANG Weizhong; HU Zhiming; XU Dapeng; YAO Zeen (He jishu, 2022)
BackgroundBoron Neutron Capture Therapy (BNCT) has been widely recognized around the world as an effective cancer treatment. The accelerator neutron source based on 7Li(p,n) reaction has the advantages of low reaction threshold, high neutron yield, low average neutron energy and easy slowing down. It is the most promising accelerator neutron source for BNCT.PurposeThis study aims to design an accelerator-based neutron source for BNCT, and design a reasonable beam shaping model.MethodsThe Geant4 (GEometry And Tracking) program was used to simulate the neutron source characteristics of protons bombarding lithium targets with different thicknesses at different energies. The accelerator parameter design scheme was proposed by using a 0.2 mm thick lithium target bombarded with 3 MeV protons. Then, the neutron beam shaping assembly (BSA) model was designed and optimized. A combination of "26 cm MgF2 + 10 cm TiF3" was taken as the moderating layer structure with 6Li of 0.08 cm taken as thermal neutron absorption layer and Bi of 1.5 cm taken as γ absorption layer. Finally, simulation of accelerator proton beam at 15 mA was carried out to calculate the optimal material combination and thickness.ResultsSimulation results show that the rate of epithermal neutron flux at the outlet of the moderator reaches 1.16×109 n·cm-2·s-1, the ratio of fast neutron to epithermal neutron Φepi / Φfast is 21.64, the ratio of thermal neutron to epithermal neutron Φepi /Φth is 125.23, and the γ component Dγ /Φepi reaches 1.82×10-13 Gy·cm2·n-1 (epi).ConclusionsThe parameters at the BSA exit designed in this study meet BNCT requirements.